Childhood trauma and neighborhood-level crime interact in predicting adult posttraumatic stress and major depression symptoms. (January 2016) - Lowe, Sarah R.; Quinn, James W.; Richards, Catherine A.; Pothen, John; Rundle, Andrew; Galea, Sandro; Ressler, Kerry J.; Koenen, Karestan C.; Bradley, Bekh
Abstract: Previous research has identified several individual-level factors that modify the risk of childhood trauma on adult psychiatric symptoms, including symptoms of major depression (MD) and posttraumatic stress (PTS). Neighborhood-level factors also influence the impact of individual-level exposures on adult psychopathology. However, no prior studies to our knowledge have explored cross-level interactions between childhood trauma and neighborhood-level factors on MD and PTS symptoms. The purpose of this study was therefore to explore cross-level interactions between a neighborhood-level factor – neighborhood-level crime – and childhood trauma on MD and PTS symptoms. Participants in this study ( N = 3192) were recruited from a large public hospital, and completed self-report inventories of childhood trauma and MD and PTS symptoms. Participant addresses were mapped onto 2010 census tracts, and data on crime within each tract were collected. Multilevel models found a significant cross-level interaction between childhood trauma and neighborhood crime on MD symptoms, such that the influence of high levels of childhood trauma on MD symptoms was enhanced for participants living in high-crime neighborhoods. Supplementary analyses found variation in the strength of cross-level interaction terms by types of childhood trauma and crime, with the strongest associations including emotional neglect paired with personal and property crime. The results provide preliminary support for interventions that help childhood trauma survivors find housing in less vulnerable neighborhoods and build skills to cope with neighborhood crime.